Pengaruh Penambahan Slag Nikel dan Fly Ash terhadap Stabilitas Tanah Lunak di Obi - Irnawaty, Irnawaty; Darwis, Muhammad; Rajab, Faisal (Jurnal Civronlit Unbari, 2025)
Soft soil is characterized by low bearing capacity, high compressibility, and significant settlement potential, which often causes problems in infrastructure development, particularly in coastal areas such as Obi Island, North Maluku. To address this issue, soil stabilization using industrial by-products has become an effective and environmentally friendly solution. Nickel slag, a by-product of nickel ore processing, and fly ash, a residue from coal combustion, have the potential to improve soil stability through both physical and chemical mechanisms. This study aims to analyze the effect of adding nickel slag and fly ash on the engineering properties of soft soil in Obi. The research method involved laboratory testing with varying proportions of nickel slag and fly ash. The tests conducted were the **Standard Proctor test** to determine the relationship between water content and soil compaction, and the **California Bearing Ratio (CALIFORNIA BEARING RATIO (CBR)) test** under soaked and unsoaked conditions to evaluate soil bearing capacity. The Proctor test results indicated that the addition of nickel slag and fly ash increased the maximum dry density and reduced the optimum moisture content compared to the untreated soil. Meanwhile, the CALIFORNIA BEARING RATIO (CBR) test results showed a significant improvement in soil strength. In the unsoaked condition, the mixture of nickel slag and fly ash increased the CALIFORNIA BEARING RATIO (CBR) value by more than 50% compared to the natural soil. Under soaked conditions, although the CALIFORNIA BEARING RATIO (CBR) values decreased, the stabilized soil still demonstrated a substantial improvement compared to untreated soil. In conclusion, the combination of nickel slag and fly ash is effective in enhancing the compaction characteristics and bearing capacity of soft soil in Obi. The contribution of this study lies not only in providing an alternative soil stabilization technique to support infrastructure development but also in promoting sustainable practices by utilizing industrial waste as a green stabilization material.